2020
DOI: 10.3390/cancers12051288
|View full text |Cite
|
Sign up to set email alerts
|

Thioholgamide A, a New Anti-Proliferative Anti-Tumor Agent, Modulates Macrophage Polarization and Metabolism

Abstract: Natural products represent powerful tools searching for novel anticancer drugs. Thioholgamide A (thioA) is a ribosomally synthesized and post-translationally modified peptide, which has been identified as a product of Streptomyces sp. MUSC 136T. In this study, we provide a comprehensive biological profile of thioA, elucidating its effects on different hallmarks of cancer in tumor cells as well as in macrophages as crucial players of the tumor microenvironment. In 2D and 3D in vitro cell culture models thioA sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 53 publications
4
35
0
Order By: Relevance
“…1A ). Macrophage polarization is characterized by distinct morphological features ( 25 ). Using H&E staining, it was identified that TAM(Ca) and TAM(CAF) exhibited an elongated morphology, which was similar to that of M2-polarized macrophages.…”
Section: Resultsmentioning
confidence: 99%
“…1A ). Macrophage polarization is characterized by distinct morphological features ( 25 ). Using H&E staining, it was identified that TAM(Ca) and TAM(CAF) exhibited an elongated morphology, which was similar to that of M2-polarized macrophages.…”
Section: Resultsmentioning
confidence: 99%
“…Monocytes were isolated and polarized as previously described [ 35 , 36 ]. In brief, peripheral blood mononuclear cells (PBMCs) were isolated from buffy coats by density gradient centrifugation using Lymphocyte Separation Medium 1077 (#C-44010, PromoCell, Heidelberg, Germany) and LeucoSEP tubes (#227290, Greiner Bio-One, Kremsmünster, Austria).…”
Section: Methodsmentioning
confidence: 99%
“…Thioholgamide A and B were initially isolated from a mangrove-derived streptomycete, Streptomyces malaysiense MUSC 136 T, and possess cytotoxic activities against cancer cell lines [75,76] . Recently, a research group in Germany has published an article studying the mechanisms involved behind the cytotoxic and anti-proliferative activities of thioholgamide A [75,77] . The team showed that thioholgamide A induces apoptosis via caspase 3 and PARP cleavage (at concentrations comparable to staurosporine) [77] .…”
Section: Data Descriptionmentioning
confidence: 99%
“…Recently, a research group in Germany has published an article studying the mechanisms involved behind the cytotoxic and anti-proliferative activities of thioholgamide A [75,77] . The team showed that thioholgamide A induces apoptosis via caspase 3 and PARP cleavage (at concentrations comparable to staurosporine) [77] . Furthermore, it appears that thioholgamide A inhibits oxidative phosphorylation in tumor cells without displaying much toxicity towards nontumorigenic cells and zebrafish embryos, thus making the compound an appealing candidate that to be developed as anti-cancer therapeutics.…”
Section: Data Descriptionmentioning
confidence: 99%